Living Qur’an, Transformasi Sosial, dan Spiritualitas: Ideologisasi Shalawat dalam Komunitas Mafia Shalawat Ponorogo - Muchlis, Ibnu (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2022)
The tradition of shalawat in Indonesia continues to evolve as an inclusive medium for spiritual and social transformation. Mafia Shalawat, a community based in Ponorogo, presents a unique approach to dakwah (Islamic propagation) through shalawat practices involving individuals from non-religious backgrounds, such as former gangsters and martial artists. Grounded in QS. Al-Ahzab: 56, this community utilizes shalawat as a means to build religious identity, foster social solidarity, and resolve societal conflicts. This study aims to examine how creative interpretations of this Qur'anic verse serve as an ideological foundation for forming a new religious habitus and creating an inclusive dakwah arena. This research employs a theoretical hermeneutic approach to objectively analyze data, which is further examined using Pierre Bourdieu's ideological theory, particularly the concepts of habitus and arena. Data were collected through in-depth interviews, participatory observations, and document studies, focusing on members of the Mafia Shalawat community actively engaged in its traditions. The findings reveal that QS. Al-Ahzab: 56 serves as the ideological basis of this community, where shalawat practices not only reinforce religious values but also drive behavioral and identity transformations among members. Traditions such as maulid recitation and regular shalawat rituals act as mechanisms for habitus formation, supported by an inclusive communal environment. This community successfully overcomes social stigmas and establishes a dakwah model that aligns with contemporary needs. In conclusion, Mafia Shalawat serves as an effective example of how Islamic traditions can be adapted to promote social harmony and spirituality in modern society. This study recommends developing similar community-based dakwah models in various contexts to expand the social and spiritual impact of religious traditions.